Productivity of Yellow fin Tuna (Thunnus albacares) catches on Hand line Vessels before the Continuation of the Covid-19 Pandemic in PPS Bungus West Sumatra Province - Sitepu, Egi Dwi Putra; Isnaniah, Isnaniah; Bustari, Bustari (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
Hand line is the simplest type of fishing gear. It consists of a fishing rod, fishing line, and weight or bait. The Coronavirus outbreak has had an impact on capture fisheries marketing, where fish prices have decreased by up to 50%. The purpose of this study is to determine whether there is an effect of the Covid 19 pandemic on the number of yellow fin tuna (Thunnus albacares) catches on hand line vessels at PPS Bungus, West Sumatra Province. Productivity of hand line trip and per crew in 2019 has the highest results and there is always a decrease in 2020, productivity per trip and crew in 2020 has decreased from 2019, again there is an increase in productivity results from 2020 - 2021 although not significant. The decline in average productivity from 2019 - 2021 is the impact of the Covid 19 Pandemic, and the factors for the decline in catch productivity are the fishing season, bad weather so that the water conditions are murky (brown) which makes it difficult to catch